1990
DOI: 10.1093/tropej/36.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Gastroenteritis in Pediatric Diarrhoea in Jos, Nigeria

Abstract: Four hundred and forty-two samples from children, age 0-5 years old, with acute diarrhoea attending hospitals and clinics in Jos between May 1986 to April 1987 were examined for the presence of rotavirus by the enzyme linked immunosorbent assay. One hundred and forty-six of these samples were positive, giving a prevalence rate of 33 per cent. The virus was more prevalent in infants 0-6 months old and decreased with an increase in age. Rotavirus was found to occur throughout the year, but there was a much highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
6
14
0
Order By: Relevance
“…A plausible explanation for this negative relationship was given by the laboratory evidence which showed that at low relative humidity, rotavirus can remain viable on plastic, glass and stainless steel for more than 10 days at room temperature (Moe and Shirley 1982;Moe and Harper 1983). The difference between both our study and the Taiwanese study (Chou et al 2010) compared to other rotavirus studies (Hashizume et al 2007b;D'Souza et al 2008;Gomwalk et al 1990) may be explained by the fact that these two studies did not analyse the relationship for bacterial and viral diarrhoea separately, and the effects of relative humidity on bacteria and virus can be different. Nevertheless, no study of a humidity-diarrhoea link has been published, so further examination of this relationship may need to be carried out in the future.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A plausible explanation for this negative relationship was given by the laboratory evidence which showed that at low relative humidity, rotavirus can remain viable on plastic, glass and stainless steel for more than 10 days at room temperature (Moe and Shirley 1982;Moe and Harper 1983). The difference between both our study and the Taiwanese study (Chou et al 2010) compared to other rotavirus studies (Hashizume et al 2007b;D'Souza et al 2008;Gomwalk et al 1990) may be explained by the fact that these two studies did not analyse the relationship for bacterial and viral diarrhoea separately, and the effects of relative humidity on bacteria and virus can be different. Nevertheless, no study of a humidity-diarrhoea link has been published, so further examination of this relationship may need to be carried out in the future.…”
Section: Discussionmentioning
confidence: 49%
“…In fact, the humiditydiarrhoea relationship was discussed in a few studies, but the findings were inconclusive. The study in Taiwan by (Chou et al 2010) found that relative humidity interacting with heavy rainfall contributed to increased risk of diarrhoea-associated morbidity among adults, whereas most of the previous studies a found a negative relationship between relative humidity and rotavirus diarrhoea among young children (Hashizume et al 2007b;Gomwalk et al 1990;D'Souza et al 2008). Their study also demonstrated that humidity alone did not significantly influence diarrhoea incidence but interacted with temperature to reduce the incidence of rotavirus diarrhoea (D'Souza et al 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Serological studies have demonstrated that 30% of infants are infected with rotavirus by age 9 months and that, in developing countries, virtually all children have been infected with rotavirus by 3-4 years of age [25][26][27][28][29]. In the present study, the average incidence of rotavirus infection among children !5 years of age was 151 cases/1000 children/year, with the highest incidence occurring among children 12-24 months of age.…”
Section: Discussionmentioning
confidence: 60%
“…[14][15][16] Rotavirus infection is endemic in Nigeria and most studies conducted are hospital based. [17][18][19][20][21][22] There are a few isolated reports on community studies 23,24 on virus-associated gastroenteritis in children in Nigeria and only a couple of reports on the prevalence of astroviruses. 15,25 The objective of this study was to determine the prevalence of rotaviruses and astroviruses and establish which strain of rotavirus circulates in Zaria, Nigeria, a community where most patients with diarrheal diseases do not visit clinics or health care centers.…”
Section: Introductionmentioning
confidence: 99%